Optimalization Route to Tourism Places in West Java Using A-STAR Algorithm - Muhammad Helambang Prakasa Yudha; Sudrajat Supian; Herlina Napitupulu (Mathematics Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Various algorithms can be used in the problem of finding the optimal route, one of which is the A-STAR Algorithm. The characteristic for recording routes that have been evaluated is one of the advantages of the A-STAR Algorithm. This study focuses on finding the optimal route to tourism places in West Java Province. In the application of the A-STAR Algorithm, distance data and density data are used from each line segment in West Java Province. The heuristic values used are converted from density data. The A-STAR algorithm is implemented using Python so that the optimal route to tourism places in West Java Province is obtained.